Need for Executive Leadership Coaching in Public Health, Healthcare Administration, Public Safety Crisis Management, and Healthcare Humanitarian Relief - Dr. Amalisha Sabie Aridi (Health Economics and Management Review, 2025)
The COVID-19 pandemic, compounded by geopolitical conflicts and climate-related disasters, has revealed profound vulnerabilities in global public health emergency response and humanitarian healthcare systems. Leadership capacity has emerged as a critical determinant of effective public health crisis management, particularly in resource allocation, crisis communication, and multidisciplinary team coordination. However, widespread variability in leaders’ adaptability and decision-making under pressure has exposed significant gaps in preparedness. This review presents an analytical overview of how established leadership theories, including the Canoe Theory for coordinated action in emergencies, the Fiedler Contingency Theory for situational crisis leadership, and the Path-Goal Theory for crisis and adaptive leadership development, can inform and enhance leadership coaching interventions in public health contexts. The novelty of this research lies in synthesizing these leadership theories with the transformative potential of artificial intelligence (AI) to advance public health leadership development. The review introduces a new model, the Healthcare Leadership Coaching Contribution Model, which consists of 28 targeted coaching focus areas tailored to public health emergency response, healthcare supply chain resilience, and organizational adaptability. This model bridges theory and practice by proposing how AI tools, including machine learning, natural language processing, and behavioral analytics, can deliver personalized, scalable coaching to cultivate leaders’ emotional intelligence, adaptive skills, and ethical decision-making during high-stakes public health emergencies. To conduct this review, we employed a rapid literature review methodology, focusing on publications from 2015 to 2025. Searches were performed across multiple scientific databases, including PubMed, Scopus, Web of Science, ResearchGate, and Google Scholar. The review proceeded through three iterative phases: 1) initial scoping to identify thematic clusters related to leadership, AI applications, and public health emergencies; 2) targeted refinement based on inclusion and exclusion criteria emphasizing public health contexts; 3) thematic coding and synthesis of articles relevant to leadership effectiveness, coaching interventions, and AI integration in crisis settings. Findings underscore the AI potential to transform leadership coaching into a dynamic, evidence-driven process capable of rapidly developing public health leaders’ competencies in crisis navigation and system resilience. AI-enabled coaching offers unprecedented opportunities to integrate predictive analytics, real-time feedback, and personalized development pathways, thereby fortifying public health systems’ capacity to respond effectively to future disruptions and protect vulnerable populations. This review advocates for the strategic adoption of AI-driven coaching as a foundational element of public health leadership development, positioning the sector for greater agility and efficacy in managing complex global health threats.